Pemanfaatan Media Pembelajaran Canva Untuk Meningkatkan Minat Literasi Membaca Peserta Didik Sekolah Dasar - Siti Filzatul Haziyah, Siti Filzatul Haziyah; Nursiwi Nughraheni, Nursiwi Nughraheni (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Education serves as a critical tool for transferring knowledge across generations and fostering national development. In Indonesia, reading plays a vital role in this educational process, yet recent reports indicate that elementary school students demonstrate only moderate literacy levels, attributed largely to low reading interest. This study investigates the impact of using Canva, an interactive online design platform, to enhance reading interest among second-grade students at SDN Ngesrep 03. Employing a descriptive qualitative approach, data were gathered through observations, interviews, and documentation over two weeks. The findings indicate that the integration of Canva into the learning process not only made lessons more engaging but also significantly increased students’ motivation to read. By transforming traditional, often monotonous teaching methods into dynamic, visually stimulating experiences, this approach effectively stimulated students' imaginations and fostered a deeper understanding of reading materials. The results suggest that utilizing modern educational media like Canva can be a viable solution to improve reading literacy and student engagement in Indonesia, ultimately contributing to better learning outcomes.